2021
DOI: 10.1155/2021/5570267
|View full text |Cite
|
Sign up to set email alerts
|

Functional Adrenocortical Adenoma in a Child with Beckwith–Wiedemann Syndrome

Abstract: Beckwith–Wiedemann syndrome (BWS) is a rare congenital condition characterized by complex overgrowth of different body parts. Children with Beckwith–Wiedemann syndrome, particularly those with hemihypertrophy, experience an increased risk of developing benign and malignant tumors. This case report presents an 18-month-old girl with features suggestive of Beckwith–Wiedemann syndrome who developed pubic hair, high levels of testosterone, and DHEAS with normal cortisol and progesterone levels. Computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Doya LJ et al [ 11 ] reported an 18-month-old female case that suffered from ACA combined with BWS. The other case is a 10-month-old female with Cushing syndrome reported by Al-Ghotani B et al [ 7 ] In this case, a 3-year-old female has ACA with isolated virilization.…”
Section: Discussionmentioning
confidence: 99%
“…Doya LJ et al [ 11 ] reported an 18-month-old female case that suffered from ACA combined with BWS. The other case is a 10-month-old female with Cushing syndrome reported by Al-Ghotani B et al [ 7 ] In this case, a 3-year-old female has ACA with isolated virilization.…”
Section: Discussionmentioning
confidence: 99%
“…The child's blood alpha-fetoprotein ( AFP) ≥2000 ng/mL during hospitalization indicates that it falls into a highrisk group. Parents should be informed of the necessity for outpatient follow-up after discharge, together with the tentative schedule outlined for the follow-up: Beckwith-Wiedemann syndrome may be accompanied by multiple malformations and the tendency of abdominal malignant tumors, 14 and thus long-term follow-up is required after the operation. Generally, outpatient follow-up is conducted once every 2 weeks after discharge, and once a month after 3 months.…”
Section: Observation Of Tumormentioning
confidence: 99%